Exact solution of thermo-mechanical analysis of laminated composite and sandwich doubly -curved shell - Monge, J. C. (2020)
This paper presents an exact solution for doubly-curved shells subjected to thermal loads. The solution is based on equilibrium equations. The through-the-thickness shell temperature is calculated using the Fourier’s heat conduction equation. The governing equations for displacement and temperature are solved using Navier method, which is valid for shell panels with constant curvature and simply-supported edges.